A new approach to fabricate superconducting NbTi alloys - Mousavi, T; Hong, Z; Morrison, A; London, AJ; Grant, PS; Grovenor, CRM; Speller, SC (Institute of Physics, 2017)
Superconducting NbTi alloys have been successfully fabricated by a simple powder processing route involving ball-milling, pressing and annealing. The microstructure and superconducting properties of the NbTi alloys after each processing step have been characterized and compared to the microstructure and performance of NbTi wire manufactured by a conventional thermo-mechanical process. At the early stages of milling, a lamellar structure of pure Nb and Ti regions is formed, which is gradually refined by further milling leading to the introduction of a high density of microstructural defects. After 20 hrs milling, diffusion of Ti into the Nb generates a matrix of -Nb-50wt%Ti alloy, with a small grain size (50 nm) and high strain (1.8% ), containing an even distribution of thin Ti flakes (10-40 nm). In some regions, these Ti flakes contain a supersaturation of Nb as a result of the energetic ball-milling process. The Tc (8.1 K) and Bc2 (9.8 T at 4.2 K) values of this as-milled material are slightly lower than those reported for Nb-47wt%Ti due to the impurity content and lattice disorder. Sintering at 400 ᵒC leads to well consolidated, high density bulk samples, but annealing at temperatures above 600 ᵒC decreases Jc values due to excessive grain growth and strain release. Annealing at lower temperatures results in higher Jc values, a shift of the pinning force density peak towards higher fields and the presence of thermodynamically stable α-Ti precipitates which are effective pinning sites leading to critical current density values comparable with those of commercial NbTi wires.